ANALISIS PEMECAHAN MASALAH MATEMATIKA PADA SISWA TIPE VISUAL BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) DI KELAS VIII SMP N 2 KOTA JAMBI - Sri Dewi (Universitas Batanghari Jambi, 2013)
In spite of using the appropriate learning approaches, there were factors that influenced to the successful in learning, namely intelligence and learning styles. RME approach and learning styles that suitable to students’ characteristics were expected to enhance students’ understanding in solving mathematical problem, which eventually leads on increasing students’ achievement. This research aimed to describe and analyse the process of students' problem solving on the type of visual-based learning RME. This study was qualitative research that used descriptive qualitative method. The research was conducted at class VIII of SMP N 2 Jambi. Subjects consisted of three students who have a visual type learning outcomes of high, medium, and low.The process of solving the problem of the study revealed through observations, interviews and task sheets based on mathematical problem solving. The data were analysed based on indicators of mathematical problem solving by Polya and noted the characteristics of the critical thinking process which included steps: (1) identification of the problem and the relevant information, (2) explored the interpretations and connections, (3) alternative prioritize and communicated the conclusions, and (4) integrated, monitored, and refined strategies for re-handling the problems.The results showed that subject of SVT and SVS could solve the issue properly, the process of solving the second problem showed in step; (1) and (2) the steps to understand the problems, arranged the problem-solving plan, implemented the plan of problem solving, and rechecked the results of problem solving. (3) the steps to understand the problems, arranged and did problem solving plan. (4) Implemented a plan and rechecked the results of problem solving. While SVR could not solve the problems correctly in step (3) and (4) in steps implemented plans and rechecked the results of problem solving.Keywords: Mathematical Problem Solving, Student Visual Mode, Realistic Mathematics Education (RME).